Malaysian fiscal policy initiative during pandemic Covid-19: a synoptic view / Mohamad Ariff Mohd Yusof ... [et al.] - Mohd Yusof, Mohamad Ariff; Azmi, Muhammad Farouk; Ismail, Junaida (2021)
The Covid-19 pandemic has evolved into a health and economic crisis of exceptional force. The situation in Malaysia is compounded by the fact that the Government came into power only in early March 2020 and is already facing a heavy debt problem, financial constraints, dropping oil prices and knock-on effects on trade and tourism from the global shut down. This paper scrutinises the fiscal policy initiative during the Covid-19 pandemic in Malaysia. According to the Board of governance and reserves system (2017) the fiscal policy refers to the tax and spending policies of the federal government. The monetary policy refers to the actions of central banks to achieve macroeconomic policy such as price stability, employment and stable economic growth. This conceptual paper provides a review from the speech by the Prime Minister of Malaysia where several initiatives under the fiscal and monetary policies were announced and implemented for the year 2020.